Automatic Quad Patch Layout Extraction for Quadrilateral Meshes. Issue 3 (3rd May 2016) - Zhang, Sen; Zhang, Hui; Yong, Jun-Hai
ABSTRACT: In this paper, we present an automatic method to extract quad patch layout with monotone boundaries in a quadrilateral mesh. Our approach simplifies the separatrices and connectivity graph topologically compared with the previous work. The key idea of our method is firstly to find all the candidates of the short separatrices based on the safety turning areas, and secondly, the problem of finding proper separatrices to extract quad patch layout is formulated as a binary integer programming problem. In the process of solving this problem, each solution is detected whether to extract quad patch layout, and finally the one with the minimum energy is determined as the global optimal solution. The produced quad patch layout is well-shaped and the corresponding base complex is coarse, which can be further used for many mesh processing applications, such as texturing, NURBS fitting and so on. GRAPHICAL ABSTRACT: